ANALISIS PELECEHAN SEKSUAL PADA FILM PENYALIN CAHAYA - Yuliana, Nia; Rorong, Michael Jibrael (LPPM Universitas Putera Batam, 2023)
Photocopier is a thriller drama film that tells about sexual harassment in the student environment, specifically the student environment. This film raises the point of view and events of a student named Suryani who has experienced a sexual crime incident which caused her to lose her scholarship from her place of study. This film also shows how to solve the problem of sexual harassment in the educational environment. This study aims to find out and describe what are the signs that describe the delivery of messages of sexual harassment in films through Pierce's 3 trichotomic categories, namely sign, object, and interpretant. The method used is Charles Sanders Pierce's semiotic theory with specialization based on icons, indexes and symbols. The research method used is a qualitative research method that produces data in verbal form, not numbers. The results of this study are that there are forms and symbols of sexual harassment that occur in the student environment, based on Charles Sanders Pierce's semiotic analysis. scenes of accumulating evidence of harassment as well as feminist ideology that is visibly raised in relation to sexual harassment.